Electronic development for a keyless anti-theft bicycle lock system prototype - Ismail I.N.; Zakariya M.A.Z.; Azman N.S.; Zawawi M.H.; Zahari N.M.; Zuhdi A.W.M.; Kamarudin K.; Zawawi M.F.M.; Basir M.H.; Hussin M.S.F. (American Institute of Physics Inc., 2023)
This study was developed using Arduino Nano that act as main brain of this system. Together with the android application that was developed use to allowed user to unlock and lock their bicycle easily by tapping the green and red button inside the application. A high security should be applied because this bicycle lock can be hack or stolen by anyone. Therefore, this project has an addition of vibration sensor and alarm to prevent theft from happening. To compare this study with top keyless bicycle company maker is far way to achieved but it is something that is not impossible to do. In this study, the objective that had to develop a keyless way to secure the bicycle lock. The software development of the keyless bicycle lock is to be based on simple yet powerful programming languages such as Arduino coding or Raspberry Pi 3 processor coding. The Bluetooth in the lock system are to be connected with the mobile phone Bluetooth software for the locking mechanism. 2021 American Institute of Physics Inc.. All rights reserved.